MiRNA‐214 is related to invasiveness of human non‐small cell lung cancer and directly regulates alpha protein kinase 2 expression. Issue 10 (9th August 2013) - Salim, Hogir; Arvanitis, Alexandros; de, Luigi; Kanter, Lena; Hååg, Petra; Zovko, Ana; Özata, Deniz Mahmut; Lui, Weng‐Onn; Lundholm, Lovisa; Zhivotovsky, Boris; Lewensohn, Rolf; Viktorsson, Kristina
<x xml:space="preserve">Abstract</x> The prognosis of non‐small cell lung cancer (NSCLC) is poor, since it has often metastasized to distant organs by the time of diagnosis. Therefore, biomarkers predicting metastasis are crucial. miRNAs play important roles in the regulation of different tumor cell processes, including metastasis. We recently showed that miRNA‐214 is linked to a radioresistant phenotype of NSCLC. miRNA‐214 has been linked to metastasis in other tumor types. Therefore, we examined the role of miRNA‐214 in the metastatic potential of NSCLC. We showed that downregulation of miRNA‐214 increased invasive potential, and conversely, overexpression of miRNA‐214 decreased invasiveness of NSCLC cells in vitro. Gene expression and bioinformatic analyses of NSCLC cells with ablated miRNA‐214, identified a number of metastasis‐related target genes, including pregnancy‐associated plasma protein A (PAPP‐A), alpha protein kinase 2 (ALPK2), cyclin‐dependent kinase 6 (CDK6) and tumor necrosis‐factor alpha‐induced protein 3 (TNFAIP3). These were validated on mRNA and protein level to be regulated by miRNA‐214. Through immunoprecipitation we showed that only ALPK2 is directly regulated by miRNA‐214. We also examined the protein expression of these four genes in NSCLC tumors with respect to metastatic potential. These results showed that NSCLC tumors express these proteins at moderate‐high levels in the nucleus, cytoplasm and/or plasma membrane although with no significant correlation to the overall survival or the metastatic potential of the patients. However, we also showed that the membrane‐localized PAPP‐A had a higher expression level compared to the cytoplasm‐localized. In conclusion, we show that low miRNA‐214 expression is linked to a higher invasive potential of NSCLC cells. © 2013 Wiley Periodicals, Inc.